Experimental evidence for the effects of dung beetle functional group richness and composition on ecosystem function in a tropical forest. - Slade, E; Mann, D; Villanueva, J; Lewis, O (2007)
Much of the literature on the relationship between species richness or functional group richness and measures of ecosystem function focuses on a restricted set of ecosystem function measures and taxonomic groups. Few such studies have been carried out under realistic levels of diversity in the field, particularly in high diversity ecosystems such as tropical forests. We used exclusion experiments to study the effects of dung beetle functional group richness and composition on two interlinked and functionally important ecological processes, dung removal and secondary seed dispersal, in evergreen tropical forest in Sabah, Malaysian Borneo. Overall, both dung and seed removal increased with dung beetle functional group richness. However, levels of ecosystem functioning were idiosyncratic depending on the identity of the functional groups present, indicating an important role for functional group composition. There was no evidence for interference or competition among functional groups. We found strong evidence for overyielding and transgressive overyielding, suggesting complementarity or facilitation among functional groups. Not all mixtures showed transgressive overyielding, so that complementarity was restricted to particular functional group combinations. Beetles in a single functional group (large nocturnal tunnellers) had a disproportionate influence on measures of ecosystem function: in their absence dung removal is reduced by approximately 75%. However, a full complement of functional groups is required to maximize ecosystem functioning. This study highlights the importance of both functional group identity and species composition in determining the ecosystem consequences of extinctions or altered patterns in the relative abundance of species.